Preparation and Characterization Study of Porous Silicon Doped with Cu and Ag - U. M. Nayef; A.M. Abdul Hussein; A. J. Kata (Engineering and Technology Journal, 2017)
In this paper, porous silicon was prepared by using electrochemical etching technique of p-type silicon acceptor, with a resistivity of 1.5-4Ohm.cm, using hydrochloric acid with concentration of 24%. The etching current density effect 4, 12, 20mA/cm2 was carried out at constant etching time of 15min. The structural characteristics of the porous silicon and the doped porous silicon were studied and found an expansion in the spectrum of the X-rays and a simple shift in the diffraction angles while maintaining the surface direction (111). The morphological properties were studied using the atomic force microscope which showed pores formation and gives the pore diameter within the range of 19.08 to 44.73nm for the prepared samples. It was also noted that the rate of pore diameter and the thickness of the porous silicon layer increased with increasing etching current density. Electrical characteristics of the nanoscale porous silicon layer and the doped porous silicon with silver and copper showed that Current-Voltage (I-V) characteristics of the prepared samples to be a rectifying behavior. An improvement in the electrical characteristics of the doped porous silicon samples was observed